STRATEGI KOMUNIKASI PT ANGKASA PURA II DALAM MENGIMPLEMENTASIKAN APLIKASI PEDULILINDUNGI SEBAGAI ACCESS CHECK-IN CONTROL BANDARA SULTAN SYARIF KASIM II PEKANBARU - Nadia Zhelvya; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Sultan Syarif Kasim II Pekanbaru Airport is one of the airports that implements health document validation rules using the PeduliLindungi application for prospective passengers during the Covid-19 pandemic. The existence of travel requirements that tend to change according to the conditions of cases of covid-19 sufferers makes people confused and lack understanding in applying them. So this study aims to find out the communication strategy of PT Angkasa Pura II in Implementing the Pedulilindungi Application as Access Check-In Control of Sultan Syarif Kasim II Pekanbaru Airport. This research uses qualitative descriptive method. Data collection is carried out by observation, interviews and documentation. The research informants were 7 people who were determined to consist of 3 people from the airport management, 2 passengers, and 2 people from the community / Influencers. Data analysis with reduction, presenting data and drawing conclusions. Checking the validity of the data using triangulation. The results showed that the communicator strategy of Sultan Syarif Kasim II Pekanbaru Airport included Customer Service, Port Health Office (KKP) officers and Airport Securit(AVSEC)y. In addition, the general public or Influencers who know information related to the PeduliLindungi application also play a role in providing information. The main audience, namely passengers, is distinguished in the aspects of the frame of reference, namely educational background, age, and situation and condition factors. The preparation of messages seen from the content of the messages conveyed tends to change in accordance with the government circular which is based on the situation of the covid-19 reduction rate, the nature of the messages packaged is more informative and persuasive, using communication media, namely social media Instagram @bandarassk2pku. Response from the public to be more active in seeking the latest information related to changes in information in the mass media.